2017
DOI: 10.1371/journal.pone.0176660
|View full text |Cite
|
Sign up to set email alerts
|

A combination of baseline plasma immune markers can predict therapeutic response in multidrug resistant tuberculosis

Abstract: ObjectiveTo identify plasma markers predictive of therapeutic response in patients with multidrug resistant tuberculosis (MDR-TB).MethodsFifty HIV-negative patients with active pulmonary MDR-TB were analysed for six soluble analytes in plasma at the time of initiating treatment (baseline) and over six months thereafter. Patients were identified as sputum culture positive or negative at baseline. Culture positive patients were further stratified by the median time to sputum culture conversion (SCC) as fast resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…A number of prospective studies have previously reported changes in biomarker levels during antitubercular treatment in either pulmonary or extrapulmonary TB cases [15,30,33,35,37,[39][40][41][49][50][51]. Our study adds to the current knowledge in the field by directly comparing these changes between PTB and EPTB disease forms while focusing on both lipid mediators and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 86%
“…A number of prospective studies have previously reported changes in biomarker levels during antitubercular treatment in either pulmonary or extrapulmonary TB cases [15,30,33,35,37,[39][40][41][49][50][51]. Our study adds to the current knowledge in the field by directly comparing these changes between PTB and EPTB disease forms while focusing on both lipid mediators and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 86%
“…A total of 51 HIV negative patients (Table 1 ) initiating treatment for MDR-TB at Sizwe Hospital in Johannesburg, South Africa were enrolled in the study, which has previously been described ( 18 ). Diagnosis of MDR-TB was based on SC (Bactec MGIT 960, Beckton Dickinson, Baltimore, MD) and phenotypic drug susceptibility testing (DST; Bactec MGIT 960) and/or genotypic resistance by PCR (Line Probe Assay, Hain Lifesciences).…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of MDR-TB was based on SC (Bactec MGIT 960, Beckton Dickinson, Baltimore, MD) and phenotypic drug susceptibility testing (DST; Bactec MGIT 960) and/or genotypic resistance by PCR (Line Probe Assay, Hain Lifesciences). Baseline (enrollment) clinical and microbiological characteristics are summarized for many of the enrolled patients ( 18 ). Nine study participants were SC negative at the time of enrollment; all of these patients were SC positive at a median of 55 days (IQR: 16.5–87.5) prior to baseline, suggesting that the infecting TB was partially responsive to first-line drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although promising, further research is needed to establish the efficacy of this new assay as marker for treatment monitoring and/or outcome. 166,195,196] [158] [172,173,197] [ 162,175] Markers of lung tissue repair (platelet activity VEGF, TGF-β, MMPs) [195,196] [135].…”
Section: T-cell Responsesmentioning
confidence: 99%